Overview of HIV Prevention among In-school Adolescents in the Rural Areas of Abia State of Nigeria - Enwereji,, E.E; Onyemechi,, P.E.N (Journal of Clinical Research In HIV AIDS And Prevention, 2021)
Introduction HIV prevention services to in-school adolescents need good planning and management. HIV risk reduction interventions are geared toward measuring sexual risk behaviour outcomes of adolescents that predispose them to HIV infection. The sexual behaviour of adolescents, especially in-school adolescents should be assessed in the process. Adolescents have been identified as the most vulnerable group for acquiring human immunodeficiency virus (HIV) and other sexually transmitted diseases (STDs) and as such, measures should be taken to prevent them from infection. One important reason for higher HIV prevalence among adolescents, especially girls, is the frequent practice of age-discrepant partnering, where older men, who are more likely to be infected with HIV, form sexual partners with younger girls. The objective of this study is to assess the knowledge and sexual behaviour of in-school adolescents in the prevention of HIV and AIDs in rural areas of Abia State. Materials and Methods This is a descriptive cross-sectional survey that was conducted between January and March 2020. Information was collected from 66 students of a community secondary school in the state. Participants were selected by a multi-stage sampling method and data were obtained using a semi-structured pre-tested questionnaire. Results Respondents consisted of 40(60.6%) females and 26(39.4%) males with ages ranging from 13 to 19. Some of the respondents 28 (42.4%), are living with parents while 24(36.4%) live with close relatives. A good number of the respondents 39(59.1%), accepted that their friends are HIV positive. Majority of them 49(74.2%) have not been approached for sexual relationships. About 17(25.8%) of the respondents accepted that they have boyfriends and girlfriends. Out of this number, 12(18.2%) of them said they have been approached for sex and only 2(3%) of them accepted having sexual relationships with the opposite sex. Finding showed that only 1(1.5%) of the respondents claimed to have ever used condoms during sex. Of the sexually active respondents, 49(74.2%) of them are aware that HIV is a virus infection caused by having multiple sex partners while 14(21.2%) were not sure whether HIV is a virus or bacterial infection. Conclusion The study revealed a gap in the knowledge of HIV prevention as well as inappropriate sexual behaviour among the respondents. Therefore, meaningful strategies that will be culturally sensitive to modify adolescent sexual risk behaviours should be adopted.
Keywords: sexual behaviour; adolescents; HIV infection; abstinence; knowledge